Pheromonal Regulation of the Reproductive Division of Labor in Social Insects - Ge, Jin; Ge, Zhuxi; Zhu, Dan; Wang, Xianhui (Frontiers in Cell and Developmental Biology, 2020)
The reproductive altruism in social insects is an evolutionary enigma that has been puzzling scientists starting from Darwin. Unravelling how reproductive skew emerges and maintains is crucial to understand the reproductive altruism involved in the consequent division of labor. The regulation of adult worker reproduction involves conspecific inhibitory signals, which are thought to be chemical signals by numerous studies. Despite the primary identification of few chemical ligands, the action modes of primer pheromones that regulate reproduction and their molecular causes and effects remain challenging. Here, these questions were elucidated by comprehensively reviewing recent advances. The synergism with other modalities of queen pheromones (QPs) and its context-dependent manner to suppress worker reproduction were discussed under the vast variation and plasticity of reproduction during colony development and across taxa. In addition to the effect of QPs, special attention was paid to recent studies revealing the regulatory effect of brood pheromones. Considering the correlation between pheromone and hormone, this study focused on the production and perception of pheromones under the endocrine control and highlighted the pivotal roles of nutrition-related pathways. The novel chemicals and gene pathways discovered by recent works provide new insights into the understanding of social regulation of reproductive division of labor in insects.